Foreign Language Communication in Virtual Exchanges: Reflections and Implications for Applied Linguistics - Salomão, Ana Cristina Biondo [UNESP] (IGI Global, 2022)
Virtual Exchange (VE) has grown out of telecollaboration, which originated in the language-teaching field and has now expanded to all areas of knowledge as a collaborative methodology to enhance learning and fostering soft skills and intercultural competences. VE has recently received growing interest from higher education institutions due to the COVID-19 pandemic and the reduction in physical mobility. This article reports a study on the strategies used by non-language specialist professors for facilitating communication in a foreign language in VE within the Brazilian Virtual Exchange (BRaVE). Data collection and analysis involved qualitative research methodology through analyzing participants' reflections. Implications for the field of applied linguistics point to the need for a theoretical framework for VE as an interdisciplinary field. This would serve the purpose to train professors to design and implement activities that involve foreign language communication.
Keywords: Applied Linguistics; BRaVE Program; Brazilian Virtual Exchange; Foreign Language Communication; Foreign Language Learning Internationalization; Telecollaboration; Virtual Exchange